An effective approach to reduce inflammation and stenosis in carotid artery: polypyrrole nanoparticle-based photothermal therapy. Issue 17 (2nd April 2015) - Peng, Zhiyou; Qin, Jinbao; Li, Bo; Ye, Kaichuang; Zhang, Yuxin; Yang, Xinrui; Yuan, Fukang; Huang, Lijia; Hu, Junqing; Lu, Xinwu
Abstract : Photothermal therapy is a promising treatment for artery restenosis, which is a common complication of endovascular management due to enduring chronic inflammation and abnormal cell proliferation. Abstract : Photothermal therapy (PTT), as a promising treatment for tumours, has rarely been reported for application in artery restenosis, which is a common complication of endovascular management due to enduring chronic inflammation and abnormal cell proliferation. In our study, biodegradable polypyrrole nanoparticles (PPy-NPs) were synthesized and characterized, including their size distribution, UV-vis-NIR absorbance, molar extinction coefficients, and photothermal properties. We then verified that PPy-NP incubation followed by 915 nm near-infrared (NIR) laser irradiation could effectively ablate inflammatory macrophages in vitro, leading to significant cell apoptosis and cell death. Further, it was found that a combination of local PPy-NP injection with 915 nm NIR laser irradiation could significantly alleviate arterial inflammation by eliminating infiltrating macrophages and further ameliorating artery stenosis in an ApoE −/− mouse model, without showing any obvious toxic side effects. Thus, we propose that PTT based on PPy-NPs as photothermal agents and a 915 nm NIR laser as a power source can serve as a new effective treatment for reducing inflammation and stenosis formation in inflamed arteries after endovascular management.